Simsalamê: vamos brincaduquê? As relações de gênero e o brincar em uma unidade municipal de educação infantil - Andréa Juliana Costa (2018)
The purpose of this study was to understand the process of constructing gender relations in the plays developed with and among children, in the age group of four and five years. The research was carried out in a Municipal Infant Education Unit (UMEI), in the municipality of Contagem in Minas Gerais and counted on the participation of eighteen children, in addition to a teacher. Some principles and procedures of the ethnographic approach were used in a phenomenological perspective, being possible to make the descriptions of the situations and dynamics inserted in the spaces and times of this institution, besides the participant observation and the individual interview with the teacher. Some references in the fields of Anthropology, Education, Psychology and Sociology corroborate with this study, such as: André (2015); Furlani (2011); Kishimoto (2016); Kramer (1999); Louro (2017); Sarmento (2008) and Xavier Filha (2009). This research pointed out that there is still a gender division in the plays developed in the space of the UMEI, being evidenced, from routine practices that, in several moments, presented subtly and, even, already naturalized, and this process was being constituted in the relationships that the children established with the teacher, with colleagues present there, as well as already carrying some conservative speeches, often from the family environment, which came to the surface, especially in moments of play. One of the possibilities pointed out in this work was the elaboration of the pedagogical material entitled Simsalamê, vamos brincaduquê?, to be made available to the team of professionals of this institution and that is associated to the context of this research, that aims, from propositions of games and their materialities that are contained within a chest, enabling adult-child mediations, while also providing more equitable gender experiences in situations involving playing in Early Childhood Education.